New essays on the nature of legal reasoning - Penner, James; McBride, Mark (London [England] : Hart Publishing, 2021)
"This is the first book to bring together distinguished jurisprudential theorists, as well as up-and-coming scholars, to critically assess the nature of legal reasoning. The volume is divided into 3 parts: The first part, General Jurisprudence and Legal Reasoning, addresses issues at the intersection of general jurisprudence - those pertaining to the nature of law itself - and legal reasoning. The second part, Rules and Reasons, addresses two concepts central to two prominent types of theory of legal reasoning. The essays in the third and final part, Doctrine and Practice, delve into the mechanics of legal practice and doctrine, from a legal reasoning perspective."--
Introduction / Mark McBride (National University of Singapore) and James Penner (National University of Singapore) -- Part I: General Jurisprudence and Legal Reasoning -- 1. On the Relationship between Law and Legal Reasoning / Fred Schauer (University of Virginia, USA) -- 2. The Law of the Street / Barbara Baum Levenbook (North Carolina State University, USA) -- 3. Must Legal Reasons be General? / Fabio Shecaira (Federal University of Rio de Janeiro, Brazil) -- 4. The Reasons Model and General Jurisprudence / Adam Rigoni (Arizona State University, USA) Part II: Rules and Reasons -- 5. No Reasons / Mark McBride (National University of Singapore) -- 6. Revisiting the Reasons Account of Precedent / Grant Lamond (University of Oxford, UK) -- 7. Visiting Revisiting Reasons (working title) / John Horty (University of Maryland, USA) -- 8. How to Govern Conduct / Larry Alexander (University of San Diego, USA) and Emily Sherwin (Cornell University, USA) -- 9. Working with a Body of Rules: On the Nature of Doctrinal Legal Disagreement in Common Law and Equity / James Penner (National University of Singapore) -- Part III: Doctrine and Practice -- 10. Thinking Like A Lawyer: An Introduction to Common Law Method / Sundram Soosay (Independent Scholar) -- 11. Square Pegs in Round Holes: Pro Se Litigants and Unjust Argument Design / Katharina Stevens (University of Lethbridge, Canada) and Nicole Lockstadt (McMaster University, Canada) -- 12. Lesser Evils, Mere Permissions and Justifying Reasons / Rob Mullins (University of Queensland, Australia) -- 13. What is a Legal Argument? An Explanation from Logocratic Metaphysics / Scott Brewer (Harvard University, USA)
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Jurisprudence; Law -- Methodology; Law -- Interpretation and construction; Reasoning; Electronic books